"Silaturahmi" According To The Jakarta Post - Pamungkas, Muhammad Ersan Pamungkas (Jurnal Penerjemahan, 2016)
This research tries to investigate how the word silaturahmi is explained in English in The Jakarta Post, a daily English language newspaper. The word silaturahmi is originally an Arabic word that has been borrowed by the Indonesian Language. By using 17 sentences containing the word silaturahmi taken from the online version of the Jakarta Post as sources of data, this research adopts a qualitative descriptive analysis to find out how the word is explained in English in the newspaper. The analysis is then compared with the meanings of silaturahmi according to the Great Dictionary of the Indonesian Language (KBBI). The result of this research shows that there are five explanations of the word silaturahmi found on the Jakarta Post as opposed to two explanations according to the KBBI. Keywords: silaturahmi, explanation, English, The Jakarta Post, KBBI